Anti-Tuberculosis Drug Resistance among New and Previously Treated Sputum Smear-Positive Tuberculosis Patients in Uganda: Results of the First National Survey - Lukoye, Deus; Adatu, Francis; Musisi, Kenneth; Kasule, George William; Were, Willy; Odeke, Rosemary; Kalamya, Julius Namonyo; Joloba, Moses L. (PloS one, 2013)
Multidrug resistant and extensively drug resistant tuberculosis (TB) have become major threats to control of tuberculosis globally. The rates of anti-TB drug resistance in Uganda are not known. We conducted a national drug resistance survey to investigate the levels and patterns of resistance to first and second line anti-TB drugs among new and previously treated sputum smear-positive TB cases.
Keywords: Anti-Tuberculosis; Drug Resistance; Treated Sputum Smear-Positive Tuberculosis Patients